2018
DOI: 10.1177/1079063218797714
|View full text |Cite
|
Sign up to set email alerts
|

Do Developmental and Life-Course Theory Risk Factors Equally Predict Age of Onset Among Juvenile Sexual and Nonsexual Offenders?

Abstract: Previous empirical inquiries into the etiology of juvenile sex offending have been largely atheoretical. Consequently, a call for studies conducted utilizing developmental and life-course (DLC) criminological theory has been made to better understand the onset, development, risk, and protective factors of juvenile sex offending. Therefore, this study contributes to the discussion by testing key predictions proposed by the DLC framework regarding the theoretical correlates of early onset offending, as applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
7
1
Order By: Relevance
“…Future research should therefore also consider separating JSOs according to the types of policies governing their sentences. Finally, although the current study did not find differences in adult criminal career parameters across different offender groups, previous research found that there were important etiological differences among JSOs according to their age of onset of sexual offending (e.g., Rosa, Fox, & Jennings, 2018). In line with the criminal career and developmental criminology emphasis on crime sequences rather than crime types, future research should examine whether juvenile sex offending onset has implications for adult criminal career parameters, including continued sexual offending in adulthood.…”
Section: Discussioncontrasting
confidence: 96%
“…Future research should therefore also consider separating JSOs according to the types of policies governing their sentences. Finally, although the current study did not find differences in adult criminal career parameters across different offender groups, previous research found that there were important etiological differences among JSOs according to their age of onset of sexual offending (e.g., Rosa, Fox, & Jennings, 2018). In line with the criminal career and developmental criminology emphasis on crime sequences rather than crime types, future research should examine whether juvenile sex offending onset has implications for adult criminal career parameters, including continued sexual offending in adulthood.…”
Section: Discussioncontrasting
confidence: 96%
“…In a similar vein, the second article in the special issue (Rosa et al, 2020) 1 also utilizes data from the United States and a sample of over 64,000 youth to offer a robust examination of the ability of developmental/life-course (DLC) risk factors to predict the age of onset for juveniles with sexual offense histories (JSOs) and juveniles with nonsex offense histories (JNSOs). Rosa et al discovered that DLC risk factors in general accurately predicted or distinguished early onset (<13 years of age) offenders from adolescent onset offenders (age 13 to age 18), although the number of DLC risk factors that predicted early onset offending for JSNOs were greater than the number of DLC risk factors that predicted early onset offending for JSOs.…”
Section: Special Issue Papersmentioning
confidence: 99%
“…As the first four articles in the special issue focused on DLC-informed risk factors for predicting recidivism (Ozkan et al, 2020), early onset offending (Rosa et al, 2020), and offending trajectories (Reale et al, 2020; Spaan et al, 2020), the fifth article in the special issue authored by Lösel and colleagues (2020) offered an evaluation of the effectiveness of in-prison treatment for persons with sexual offense histories in Germany. Lösel et al (2020) performed a methodologically robust propensity score matching algorithm to statistically create a matched sample of “similarly situated” persons with sexual offense histories groups (treatment group: n = 352; control group; n = 352).…”
Section: Special Issue Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the aforementioned concerns and conflicting figures on incidence, the number of scientific publications on JSOs has increased significantly in recent years-going from "a handful" before the mid-1980s to more than 200 published studies by 2009 (Budd & Bierie, 2018;Finkelhor et al, 2009;van Wijk et al, 2006). Even so, reliable information on many aspects of JSOs remains limited (Fox & Delisi, 2018) meaning that further exploration of the risk factors, appropriate prevention strategies, and effective treatment programs related to JSOs is highly warranted (Riser et al, 2013;Rosa et al, 2018). Furthermore, the degree of distinctiveness of juvenile sex offendersthat is, whether they are significantly different from other juvenile offenders as a group-continues to be a critically important unresolved empirical question (Blokland & Lussier, 2015).…”
Section: Introductionmentioning
confidence: 99%